2019
DOI: 10.47405/aswj.v4i3.99
|View full text |Cite
|
Sign up to set email alerts
|

Demands and Factors Associated to Psychosocial Support of Cancer Patients at Vietnam National Cancer Hospital

Abstract: Cancer patients in Vietnam are increasing exponentially in numbers, with great demands for psychosocial support. This study explored the demands for the psychosocial support of cancer patients at Vietnam National Cancer Hospital and several associated factors. This is a cross-sectional survey, qualitative and quantitative study, and conducted from April to September 2017. This study utilized the structured questionnaire of 418 cancer patients, 8 in-depth interviews and 3 focus group discussions. Results of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…At present, palliative and supportive care, responsibility falls on the ICC, with 90% of patients dying at home being cared for by their families. As a result of rising numbers, limited resources and lack of infrastructure, the information and psychosocial support needs for both patients and their families remain highly prevalent and unmet (14).…”
mentioning
confidence: 99%
“…At present, palliative and supportive care, responsibility falls on the ICC, with 90% of patients dying at home being cared for by their families. As a result of rising numbers, limited resources and lack of infrastructure, the information and psychosocial support needs for both patients and their families remain highly prevalent and unmet (14).…”
mentioning
confidence: 99%
“…When they use many negative emotion words, empathy can help them to overcome their uncertainty and despair. Pham et al (2019) found that cancer patients in the bargaining stage need the support of medical staff and social workers to strengthen their hope of overcoming the disease, while those who are in the shock and denial stages need the most support. This study is constrained by what the cancer survivors can remember at the time of the interview.…”
Section: Discussionmentioning
confidence: 99%
“…In Vietnam, 26.4% and 31.2% of lung cancer inpatients reported clinically significant depression and anxiety symptoms, respectively (defined as meeting a threshold of 8 on the Hospital Anxiety and Depression Scale [HADS]) 5 . Additionally, prior literature demonstrates that a majority of cancer patients express a need for psychological support, with 68.4% of patients showing a desire for psychological consultation and counseling 6 . Crucially, addressing psychopathological presentation in cancer patients shows promise in improving quality of life and life expectancy 7 .…”
Section: Introductionmentioning
confidence: 99%
“…5 Additionally, prior literature demonstrates that a majority of cancer patients express a need for psychological support, with 68.4% of patients showing a desire for psychological consultation and counseling. 6 Crucially, addressing psychopathological presentation in cancer patients shows promise in improving quality of life and life expectancy. 7 However, currently, the treatment gap is unacceptably large, with 77.6%, 88.6%, and 96.3% of adults with major depressive disorders not receiving minimally appropriate treatment in high-income, uppermiddle, and low/lower-middle-income countries, respectively.…”
mentioning
confidence: 99%